Gemcitabine as second-line chemotherapy after Folfirinox failure in advanced pancreatic adenocarcinoma: A retrospective study. Issue 6 (June 2017) - Viaud, Juliette; Brac, Clémence; Artru, Pascal; Le Pabic, Estelle; Leconte, Bérengère; Bodère, Anaïs; Pracht, Marc; Le Sourd, Samuel; Edeline, Julien; Lièvre, Astrid
Abstract: Background: Pancreatic adenocarcinoma (PA) is diagnosed in most cases at an advanced stage requiring chemotherapy. Folfirinox is the standard first-line treatment. After Folfirinox failure, gemcitabine alone is routinely used as second-line therapy without data supporting this attitude. Aim: Determine the response rate and outcome of patients with advanced PA treated with gemcitabine after Folfirinox failure. Methods: We retrospectively analyzed all consecutive patients treated with gemcitabine after Folfirinox failure for a locally advanced or metastatic PA between 2009 and 2015. Progression-free survival (PFS) and overall survival (OS) were calculated using the Kaplan–Meier method. Response rate, control rate and tolerability were assessed. Results: 96 patients were included (male, 51%; median age, 62; performance status (PS) 0–1, 47%). Median duration on gemcitabine was 2.1 months. The overall disease control rate was 40%. Median OS was 3.7 months (95%CI: 2.5–5.2) and median PFS was 2.1 months (95%CI: 2.0–2.6). Reasons for treatment discontinuation were mostly progression (51%). Age at diagnosis and PS were independently associated with OS in multivariate analysis (HR of 1.86; p = 0.0055 and 2.42; p < 0.0001 respectively). 34 patients experienced a grade 3 adverse event. Conclusions: This study suggests that gemcitabine is not beneficial to all patients failing on Folfirinox first-line therapy and should be restricted to young patients with good PS.